Pseudomembranous colitis in a pregnant woman - Mridula, T; Pai, R R; Mathai, A M; Tantry, B V; Adhikari, P (Kathmandu University Medical Journal, 2012)
Pseudomembranous colitis in association with pregnancy has not been well described in English literature. Recent studies show a drastic increase in the incidence and severity of Pseudomembranous colitis in pregnant women, who were once thought to be at low risk. We report here a case of Pseudomembranous colitis in a young healthy immunocompetent pregnant lady. An early suspicion of this entity with the characteristic appearance of pseudomembranes on colonoscopy and histology confirmed the diagnosis enabling prompt treatment and complete recovery without any serious consequences. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6226 Kathmandu Univ Med J 2010;8(3):345-7